1998 IEEE Nuclear Science Symposium Conference Record. 1998 IEEE Nuclear Science Symposium and Medical Imaging Conference (Cat.
DOI: 10.1109/nssmic.1998.773835
|View full text |Cite
|
Sign up to set email alerts
|

High energy 3-D nuclear medicine imaging using coded apertures with a conventional gamma camera

Abstract: Standard nuclear medicine imaging uses photon collimation and thus suffer from very low sensitivity, especially if high energy (>511 KeV) isotopes are to be imaged. Coded aperture techniques use a coded pattern mask instead of a collimator to encode the photon source distribution, thus every photon source contributes to the signal in the whole detector area. It significantly improves the system sensitivity while retaining the spatial resolution of the reconstructed images. We have developed coded aperture arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Fig. 5(c) shows the same image further corrected for the collimation effect by the expressed in (18). As shown in Fig.…”
Section: B Angular Compensation and Collimation Correction For Mask mentioning
confidence: 95%
See 3 more Smart Citations
“…Fig. 5(c) shows the same image further corrected for the collimation effect by the expressed in (18). As shown in Fig.…”
Section: B Angular Compensation and Collimation Correction For Mask mentioning
confidence: 95%
“…A complete representation of the collimation effect is an average of all possible incident rays passing through the mask expressed as (18) Notice that above is an average of all possible rays with the implicit assumption that all possible rays exist and are of equal intensity. However, this is not always true.…”
Section: B Near-field Ca Imaging and Aperture Collimation Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of partial 3D reconstruction from a single coded aperture projection have been reported previously by others. [16][17][18][19] However, these methods produced low quality images with poor resolution along the depth direction. Meikle et al reported their studies on coded aperture SPECT for small animal imaging and provided useful perspectives on numerous system designs.…”
Section: Introductionmentioning
confidence: 99%